Black high-thermal-conductivity aluminum nitride ceramic and preparation method thereof

By improving the preparation process of aluminum nitride ceramics, and using methods of precise control of atmosphere sintering and multi-stage temperature control, the problem that aluminum nitride ceramics in the prior art is difficult to take into account high thermal conductivity and black properties, and the dual performance modification of high thermal conductivity and significant black properties is achieved.

CN119874380AActive Publication Date: 2025-04-25JIANGSU BREE OPTRONICS CO LTD

Patent Information

Application Number
CN202411883925.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing aluminum nitride ceramics are difficult to take into account both high thermal conductivity and black properties, and colorants will affect thermal conductivity in conventional preparation processes.

Method used

By improving the preparation process, using a method of precisely controlling atmosphere sintering, combined with multi-stage temperature control and the use of different atmospheres, the adverse effects of colorants on thermal conductivity are hindered, and the modification of black and high thermal conductivity of aluminum nitride ceramics is achieved.

Benefits of technology

The modification of aluminum nitride ceramics in both high thermal conductivity and black properties is achieved, ensuring the high thermal conductivity of the product (not less than 180W/m·k) and significant black (reflectivity does not exceed 14%).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198831660000141
    Figure BDA0005198831660000141
  • Figure BDA0005198831660000151
    Figure BDA0005198831660000151
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum nitride ceramic manufacturing, and particularly discloses black high-thermal-conductivity aluminum nitride ceramic and a preparation method thereof. The black aluminum nitride ceramic with high thermal conductivity is prepared by uniformly mixing and sintering aluminum nitride powder, a sintering aid and a coloring aid in a mass ratio of (90-98): (1-5): (1-5), and has the reflectivity of not more than 14% and the thermal conductivity of more than 180W / m.k. According to the preparation method, on the basis that the coloring auxiliary provides black modification for aluminum nitride, through accurate control over the oxygen content in a rubber discharging sheet obtained through rubber discharging, the multi-stage temperature end point in the sintering process and different atmospheres in the rubber discharging and sintering processes, the adverse effect of the coloring auxiliary on the improvement of the heat conductivity is hindered, and the thermal conductivity is improved. And the obtained aluminum nitride ceramic is ensured to have both black and high thermal conductivity. The raw materials required by the preparation method are conventional and easy to obtain, the process is simple, the cost is low, and the preparation method is convenient to popularize in the fields with high heat conduction and special requirements on light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum nitride ceramic manufacturing, and in particular, relates to a black high thermal conductivity aluminum nitride ceramic having both black color and high thermal conductivity, and a preparation method thereof. Background Art

[0002] At present, aluminum nitride ceramics are mostly translucent, with a yellowish or grayish color. Ordinary aluminum nitride ceramics are mostly used on LED packaging substrates, while a small amount of high thermal conductivity aluminum nitride ceramics are used in the field of laser heat sinks.

[0003] Black ceramics are currently mainly alumina black ceramics, which are used in multilayer ceramic circuits, optoelectronics, digital integrated circuits, microwaves, optical communications, crystal oscillator device ceramic housings and other fields. However, due to the low thermal conductivity of black alumina ceramics, they cannot meet the thermal conduction needs of high-power, high-density devices and power devices with special requirements for heat absorption and light avoidance.

[0004] Although there are related studies on high thermal conductivity aluminum nitride ceramics and black aluminum nitride ceramics, it is often impossible to take into account the dual properties of high thermal conductivity and black in aluminum nitride ceramics. Therefore, an aluminum nitride ceramic with both high thermal conductivity and black (blackness) characteristics can not only meet the needs of high thermal conduction, but also be used in fields with special requirements for light. It is necessary to conduct further research on the preparation of black high thermal conductivity aluminum nitride ceramics. Summary of the invention

[0005] In view of the problem that the modification of aluminum nitride ceramics in the prior art is only aimed at the single performance of high thermal conductivity or black color, the inventors of the present invention, based on long-term research on aluminum nitride ceramics, found that the main reason why the two cannot be taken into account is that the preparation of black ceramics often requires the addition of colorants, but under conventional preparation processes, colorants will have an adverse effect on thermal conductivity and hinder the improvement of thermal conductivity; for this reason, through the improvement of the preparation process, a black high thermal conductivity aluminum nitride ceramic and its preparation method are proposed. This preparation method, through precise control of atmosphere sintering, ensures the high thermal conductivity of aluminum nitride ceramics while also having blackness, and realizes the modification of aluminum nitride ceramics in the dual properties of high thermal conductivity and black color.

[0006] The present invention specifically adopts the following technical solutions:

[0007] A black high thermal conductivity aluminum nitride ceramic is prepared by uniformly mixing and sintering aluminum nitride powder, a sintering aid and a coloring aid in a mass ratio of 90-98:1-5:1-5, and has a reflectivity of no more than 14% and a thermal conductivity of more than 180 W / m·k.

[0008] Obviously, the reflectivity of no more than 14% ensures that the aluminum nitride ceramic presents an obvious black color and belongs to the category of black ceramics.

[0009] The aluminum nitride powder used as the raw material generally uses AlN powder with an oxygen content not higher than 0.7%, and the oxygen content of the aluminum nitride powder before sintering is controlled to be no more than 1.9%.

[0010] The sintering aid is selected from a mixture of at least two of Y2O3, CaF, CaO, MgO, ZnO, and SiO2. For example, it can be a mixture of two such as Y2O3 and CaF2, or Y2O3 and MgO, or a mixture of three such as Y2O3, CaO and MgO, or Y2O3, ZnO and SiO2, which will not be described in detail here.

[0011] The coloring aid is selected from any one of CeO2, MnO2, MoO2, MoO3, Fe2O3, Fe3O4, Cr2O3, NbO2, HfO2, DyO2, TiO2, Co3O4, GaO2, or a mixture of at least two thereof. For example, it may be a single MnO2, MoO3, etc., or a mixture of two such as NbO2 and Mo2O3, or MnO2 and MoO3, or a mixture of three such as TiO2, Cr2O3 and Ga2O3, or Co3O4, Cr2O3 and NbO2, etc., which will not be described in detail here.

[0012] Preferably, the black high thermal conductivity aluminum nitride ceramic also includes a dispersant, such as one selected from oleic acid, herring oil, acrylate, phosphate, etc. The addition of the dispersant does not affect the thermal conductivity and color rendering of the final aluminum nitride ceramic. Generally, the amount of the dispersant added is controlled to be 1% to 5% of the total mass of the aluminum nitride powder, sintering aid and coloring aid, and those skilled in the art can implement it according to the general records in the prior art.

[0013] The present invention also provides a method for preparing the above-mentioned black high thermal conductivity aluminum nitride ceramic, comprising the following steps:

[0014] S1, mixing and ball-milling a sintering aid, a coloring aid, aluminum nitride powder, a binder and a solvent to obtain a tape-casting slurry;

[0015] S2, vacuum degassing the casting slurry to a viscosity of 5000m·Pa·s to 18000m·Pa·s, and then casting to obtain a green sheet;

[0016] S3, heating the green sheet to 300° C. to 600° C. under an inert gas or an inert-air mixed gas, and controlling the process from the beginning of the heating to perform debinding for at least 10 hours to obtain a debinded sheet with an oxygen content not exceeding 1.9%;

[0017] S4. Raise the temperature of the film to 1400°C~1600°C once, and introduce an inert-reducing mixed gas for at least 60 minutes before reaching this temperature to carry out a color development reaction, then raise the temperature to 1650°C~1950°C for a second time for at least 90 minutes, and finally keep the temperature for 3h~100h, and ensure that the total duration of the second heating and heat preservation is not less than 10h, to complete the sintering and obtain black high thermal conductivity aluminum nitride ceramics.

[0018] Specifically, in step S1 , the casting slurry is obtained by mixing the composite colloid and the sintering powder and ball milling them.

[0019] Furthermore, the preparation method of the sintered powder is: mixing and ball-milling a sintering aid, a coloring aid, aluminum nitride powder and a first solvent to obtain the sintered powder.

[0020] Furthermore, the mass ratio of the aluminum nitride powder, the sintering aid and the coloring aid is 90-98:1-5:1-5, and the mixture of the three is defined as ceramic powder.

[0021] Generally, the mass ratio of the ceramic powder to the first solvent is controlled to be 1:0.4-0.8.

[0022] Furthermore, the preparation method of the composite colloid is: uniformly mixing the binder and the second solvent to obtain the composite colloid.

[0023] Generally, the mass ratio of the binder to the second solvent is controlled to be 1:3-7.

[0024] The “solvent” in the above step S1 includes the first solvent and the second solvent.

[0025] Wherein, in the preparation of the casting slurry in step S1, the mass ratio of the binder to the ceramic powder is 0.05-0.12:1.

[0026] Among them, in step S3, the debinding process can be to adopt a slower heating rate to reach the temperature of 300℃~600℃ in the next step (one-step method), or to perform appropriate insulation operation after reaching the temperature of 300℃~600℃, or to adopt a faster heating rate to reach the final temperature of 300℃~600℃ in stages and set an insulation section during the period (multi-step-insulation platform method), or the above-mentioned one-step method or multi-step-insulation platform method is combined with the insulation procedure after heating, so as to achieve a total operation time of at least 10 hours and control the oxygen content of the debinding sheet within the range of no more than 1.9%.

[0027] In step S4, before the color development reaction begins, during the secondary heating process and the subsequent heat preservation process, inert gas or inert-reducing mixed gas is used. When the secondary heating process and the subsequent heat preservation process use a mixed gas, the reducing gas therein can be further used to reduce the oxygen content, thereby improving the thermal conductivity.

[0028] The above-mentioned inert-reducing mixed gas refers to a mixed gas of an inert gas and a reducing gas.

[0029] Generally, the inert gas can be selected from conventional inert gases such as nitrogen, argon, helium, etc., and the reducing gas can be selected from hydrogen or carbon monoxide.

[0030] Furthermore, in step S4, in the inert-reducing mixed gas introduced during the color development reaction, the volume content of the reducing gas introduced accounts for 4% to 15% of the total volume of the inert-reducing mixed gas.

[0031] Furthermore, in step S4, the heating process can be a one-step method to reach a temperature of 1400°C to 1600°C at a slower heating rate, or a moderate heat preservation operation after reaching a temperature of 1400°C to 1600°C, or a faster heating rate to reach the final temperature of 1400°C to 1600°C in stages and a heat preservation section during the process (multi-step-heat preservation platform method), or a combination of the above-mentioned one-step method or multi-step-heat preservation platform method with a heat preservation procedure after heating.

[0032] Furthermore, in step S4, the secondary heating process can be to use a slower heating rate to reach a temperature of 1650°C to 1950°C in one step (one-step method), or to use a faster heating rate to reach the final temperature of 1650°C to 1950°C in stages and set a heat preservation section during the period (multi-step-heat preservation platform method), so as to achieve a total secondary heating time of at least 60 minutes.

[0033] Generally, part of the above dispersant is added during the preparation of sintered powder to make the powder materials dispersed more evenly.

[0034] Generally, in the preparation process of the composite colloid, some plasticizers may be added, such as DOP and / or DBP. The addition of the plasticizer does not affect the thermal conductivity and color rendering of the final aluminum nitride ceramic. Generally, the amount of the plasticizer added is controlled to be 0.5 to 1.2 times the mass of the binder, and those skilled in the art may implement it according to the general records in the prior art.

[0035] Wherein, the binder is selected from polyvinyl butyral and / or polyacrylic acid resin.

[0036] The first solvent and the second solvent are selected from any one of xylene, toluene, methanol, ethanol, isopropanol, n-butanol, acetone, ethyl acetate, methyl ethyl ketone, trichloroethane, and cyclohexanone, or a mixture of at least two thereof. For example, it can be a single solvent such as toluene, acetone, ethanol, isopropanol, etc., or a mixed solvent such as toluene and isopropanol, or butanone and ethanol, or ethyl acetate and ethanol, etc., which will not be described one by one here.

[0037] When the first solvent and the second solvent are a mixture of two solvents, the ratio of the two solvents is not limited, for example, 2:3, 3:2, 3:4, etc. can be used.

[0038] The above-mentioned black high thermal conductivity aluminum nitride ceramic and the preparation method thereof provided by the present invention, on the basis of providing black modification for aluminum nitride by the coloring auxiliary agent, through the precise control of the degree of binder removal (oxygen content in the binder removal sheet), the multi-stage temperature end point during the sintering process, and the different atmospheres during the binder removal and sintering process, the adverse effect of the coloring auxiliary agent on the improvement of thermal conductivity is hindered, and it is ensured that the obtained aluminum nitride ceramic has both black color (reflectivity not exceeding 14%) and high thermal conductivity of more than 180W / m·k.

[0039] Specifically, firstly, by controlling the atmosphere during the debinding process, the increase in oxygen content in aluminum nitride after the debinding process is controlled, and the proportion of the second phase of aluminum nitride in the subsequent sintering process is reduced, thereby ensuring that the thermal conductivity of aluminum nitride ceramics is higher; secondly, by controlling the staged heating and sintering atmosphere during the sintering process, the doping reaction of the coloring additive and the price of the coloring element are carried out in advance, and by regulating different sintering atmospheres and times, the oxygen impurity content of the aluminum nitride lattice is reduced during the high-temperature grain growth of aluminum nitride, thereby promoting grain growth and improving the thermal conductivity of the ceramic. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field under the premise of creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0043] First, 1.5 g of Y2O3 powder and 0.5 g of CaF2 powder were weighed and mixed as a sintering aid, and 0.3 g of NbO2 powder and 0.7 g of Mo2O3 powder were weighed and mixed as a coloring aid.

[0044] Then, the sintering aid, coloring aid and 1.5 g oleic acid were mixed with 45 g toluene-isopropanol mixed solvent and wet pre-ball-milled for 2 h, and then 97 g aluminum nitride powder (oxygen content 0.65%) was added and ball-milled to obtain sintered powder.

[0045] That is, the mass ratio of the total amount of the ceramic powder consisting of the sintering aid, the coloring aid and the aluminum nitride powder to the toluene-isopropanol mixed solvent used to disperse the ceramic powder is 1:0.45.

[0046] Next, 8 g of polyacrylic acid resin and 4 g of DBP were dissolved in 28 g of a toluene-isopropanol mixed solvent to prepare a polyacrylic acid solution as a composite colloid.

[0047] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0048] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the mass ratio of the polyacrylic acid resin in the composite colloid is 100:8.

[0049] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 11000 m·Pa·s, and to obtain a green sheet by tape casting.

[0050] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.6%.

[0051] Specifically, the temperature was increased to 300°C at a heating rate of 0.5°C / min at a nitrogen ventilation flow rate of 800L / min and kept warm for 1h, and then the temperature was increased to 350°C at a heating rate of 0.05°C / min at a nitrogen-air mixed gas ventilation flow rate of 800L / min (600L / min nitrogen + 200L / min air) and kept warm for 1h to complete the debinding.

[0052] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0053] Specifically, the temperature was increased to 1000°C at a heating rate of 6°C / min under nitrogen, then increased to 1600°C at a heating rate of 2°C / min under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen was 9:1), and finally increased to 1750°C at a heating rate of 0.3°C / min under nitrogen, and kept for 12 hours under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen was 9.6:0.4) to complete the sintering.

[0054] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 97% aluminum nitride, 2% sintering aid (including 1.5% Y2O3 and 0.5% CaF2) and 1% coloring aid (including 0.3% NbO2 and 0.7% Mo2O3).

[0055] Example 2

[0056] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0057] First, 4 g of Y2O3 powder, 0.5 g of CaO powder and 0.5 g of MgO were weighed and mixed as a sintering aid, and 1.5 g of TiO2 powder, 2 g of Cr2O3 powder and 0.5 g of Ga2O3 powder were weighed and mixed as a coloring aid.

[0058] Then, the sintering aid, coloring aid and 4 g of phosphate were mixed with 75 g of a mixed solvent of butanone and anhydrous ethanol and dispersed by wet pre-ball milling for 3 h, and then 91 g of aluminum nitride powder (oxygen content of 0.65%) was added and dispersed by ball milling to obtain sintered powder.

[0059] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the butanone-anhydrous ethanol mixed solvent used to disperse the ceramic powder is 1:0.75.

[0060] Next, 5.5 g of polyacrylic acid resin and 6 g of DOP were dissolved in 38 g of a mixed solvent of butanone and anhydrous ethanol to prepare a polyacrylic acid solution as a composite colloid.

[0061] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0062] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the mass ratio of the polyacrylic acid resin in the composite colloid is 100:10.

[0063] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 5000 m·Pa·s, and to obtain a green sheet by tape casting.

[0064] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.85%.

[0065] Specifically, the temperature was increased to 250°C at a heating rate of 0.3°C / min under a nitrogen ventilation flow rate of 600L / min and kept warm for 1 hour, and then the temperature was increased to 580°C at a heating rate of 0.15°C / min under a nitrogen flow rate of 600L / min and kept warm for 1 hour to complete the debinding.

[0066] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0067] Specifically, the temperature was increased to 1400°C at a heating rate of 10°C / min in a nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 8.5:1.5), and then kept at 1400°C for 30 minutes. Finally, the temperature was increased to 1700°C at a heating rate of 0.6°C / min in a nitrogen atmosphere, and kept for 100 hours in a nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 9.5:0.5) to complete the sintering.

[0068] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 91% aluminum nitride, 5% sintering aid (including 4% Y2O3, 0.5% CaO and 0.5% MgO) and 4% coloring aid (including 1.5% TiO2, 2% Cr2O3 and 0.5% Ga2O3).

[0069] Example 3

[0070] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0071] First, 2 g of Y2O3 powder and 0.8 g of MgO were weighed and mixed as a sintering aid, and 0.4 g of Co3O4 powder, 0.4 g of Cr2O3 powder and 0.2 g of NbO2 powder were weighed and mixed as a coloring aid.

[0072] Then, the sintering aid, coloring aid and 2g oleic acid were mixed with 80g ethyl acetate-anhydrous ethanol mixed solvent and wet pre-ball-milled for 3h, and then 96.2g aluminum nitride powder (oxygen content 0.5%) was added and ball-milled to obtain sintered powder.

[0073] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the ethyl acetate-anhydrous ethanol mixed solvent used to disperse the ceramic powder is 1:0.8.

[0074] Next, 5 g of polyacrylic acid resin and 4 g of DBP were dissolved in 25 g of a mixed solvent of ethyl acetate and anhydrous ethanol to prepare a polyacrylic acid solution as a composite colloid.

[0075] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0076] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the mass ratio of the polyacrylic acid resin in the composite colloid is 100:5.

[0077] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 18000 m·Pa·s, and to obtain a green sheet by tape casting.

[0078] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.35%.

[0079] Specifically, the temperature was increased to 250°C at a heating rate of 0.7°C / min at a nitrogen flow rate of 600 L / min and kept warm for 1 hour, and then the temperature was increased to 450°C at a heating rate of 0.15°C / min at a nitrogen flow rate of 600 L / min and kept warm for 3 hours to complete the debinding.

[0080] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0081] Specifically, the temperature was increased to 800°C under nitrogen at a heating rate of 10°C / min, then increased to 1600°C under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 8.5:1.5) at a heating rate of 3°C / min, and finally increased to 1780°C under nitrogen at a heating rate of 0.3°C / min, and kept for 20 hours under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 9.5:0.5) to complete the sintering.

[0082] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 96.2% aluminum nitride, 2.8% sintering aids (including 2% Y2O3 and 0.8% MgO) and 1% coloring aids (including 0.4% Co3O4, 0.4% Cr2O3 and 0.2% NbO2).

[0083] Example 4

[0084] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0085] First, 2.5 g of Y2O3 powder and 0.5 g of CaF2 powder were weighed and mixed as a sintering aid, and 0.3 g of NbO2 powder and 0.7 g of Mo2O3 powder were weighed and mixed as a coloring aid.

[0086] Then, the sintering aid, coloring aid and 2g oleic acid were mixed with 60g toluene-isopropanol mixed solvent and wet pre-ball-milled for 2h, and then 96g aluminum nitride powder (oxygen content 0.65%) was added and ball-milled to obtain sintered powder.

[0087] That is, the mass ratio of the total amount of the ceramic powder consisting of the sintering aid, the coloring aid and the aluminum nitride powder to the toluene-isopropanol mixed solvent used to disperse the ceramic powder is 1:0.6.

[0088] Next, 7 g of polyacrylic acid resin and 6 g of DBP were dissolved in 42 g of a toluene-isopropanol mixed solvent to prepare a polyacrylic acid solution as a composite colloid.

[0089] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0090] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the polyacrylic acid resin in the composite colloid is 100:7.

[0091] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 11000 m·Pa·s, and to obtain a green sheet by tape casting.

[0092] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.5%.

[0093] Specifically, the temperature was increased to 250°C at a heating rate of 1°C / min at a nitrogen ventilation flow rate of 600L / min and kept warm for 1h, and then the temperature was increased to 500°C at a heating rate of 0.8°C / min at a nitrogen-air mixed gas ventilation flow rate of 700L / min (600L / min nitrogen + 100L / min air) and kept warm for 1h to complete the debinding.

[0094] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0095] Specifically, the temperature was increased to 1000°C under nitrogen at a heating rate of 10°C / min, then increased to 1550°C under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 9.5:0.5) at a heating rate of 8°C / min, and finally increased to 1850°C under nitrogen at a heating rate of 0.5°C / min, and kept for 20 hours under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen was 9.5:0.5) to complete the sintering.

[0096] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 97% aluminum nitride, 2% sintering aid (including 1.5% Y2O3 and 0.5% CaF2) and 1% coloring aid (including 0.3% NbO2 and 0.7% Mo2O3).

[0097] Example 5

[0098] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0099] First, 2.5 g of Y2O3 powder and 0.5 g of CaF2 powder were weighed and mixed as a sintering aid, and 0.3 g of NbO2 powder and 0.7 g of Mo2O3 powder were weighed and mixed as a coloring aid.

[0100] Then, the sintering aid, coloring aid and 3g oleic acid were mixed with 60g toluene-isopropanol mixed solvent and wet pre-ball-milled for 2h, and then 96g aluminum nitride powder (oxygen content 0.65%) was added and ball-milled to obtain sintered powder.

[0101] That is, the mass ratio of the total amount of the ceramic powder consisting of the sintering aid, the coloring aid and the aluminum nitride powder to the toluene-isopropanol mixed solvent used to disperse the ceramic powder is 1:0.6.

[0102] Next, 7 g of polyacrylic acid resin and 6 g of DBP were dissolved in 42 g of a toluene-isopropanol mixed solvent to prepare a polyacrylic acid solution as a composite colloid.

[0103] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0104] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the polyacrylic acid resin in the composite colloid is 100:7.

[0105] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 11000 m·Pa·s, and to obtain a green sheet by tape casting.

[0106] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.35%.

[0107] Specifically, the temperature was increased to 250°C at a heating rate of 0.7°C / min under a nitrogen ventilation flow rate of 600 L / min and kept warm for 1 hour, and then the temperature was increased to 450°C at a heating rate of 0.15°C / min under a nitrogen flow rate of 600 L / min and kept warm for 3 hours to complete the debinding.

[0108] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0109] Specifically, the temperature was increased to 800°C at a heating rate of 10°C / min under nitrogen, and then increased to 1600°C at a heating rate of 3°C / min under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen was 8.5:1.5), and finally increased to 1800°C at a heating rate of 0.3°C / min under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen was 9.5:0.5), and kept for 3 hours to complete the sintering.

[0110] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 97% aluminum nitride, 2% sintering aid (including 1.5% Y2O3 and 0.5% CaF2) and 1% coloring aid (including 0.3% NbO2 and 0.7% Mo2O3).

[0111] Example 6

[0112] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0113] First, 4 g of Y2O3 powder and 1 g of CaF2 powder were weighed and mixed as a sintering aid, and 0.3 g of NbO2 powder and 0.7 g of Mo2O3 powder were weighed and mixed as a coloring aid.

[0114] Then, the sintering aid, coloring aid and 1.5 g oleic acid were mixed with 45 g toluene-isopropanol mixed solvent and wet pre-ball-milled for 2 h, and then 94 g aluminum nitride powder (oxygen content 0.65%) was added and ball-milled to obtain sintered powder.

[0115] That is, the mass ratio of the total amount of the ceramic powder consisting of the sintering aid, the coloring aid and the aluminum nitride powder to the toluene-isopropanol mixed solvent used to disperse the ceramic powder is 1:0.45.

[0116] Next, 8 g of polyacrylic acid resin and 4 g of DBP were dissolved in 28 g of a toluene-isopropanol mixed solvent to prepare a polyacrylic acid solution as a composite colloid.

[0117] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0118] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the mass ratio of the polyacrylic acid resin in the composite colloid is 100:8.

[0119] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 11000 m·Pa·s, and to obtain a green sheet by tape casting.

[0120] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.75%.

[0121] Specifically, the temperature was increased to 300°C at a heating rate of 0.5°C / min at a nitrogen ventilation flow rate of 800L / min and kept warm for 1h, and then the temperature was increased to 350°C at a heating rate of 0.05°C / min at a nitrogen-air mixed gas ventilation flow rate of 800L / min (750L / min nitrogen + 50L / min air) and kept warm for 1h to complete the debinding.

[0122] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0123] Specifically, the temperature was increased to 1000°C at a heating rate of 6°C / min under nitrogen, then increased to 1600°C at a heating rate of 2°C / min under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen is 9:1), and finally increased to 1750°C at a heating rate of 1.5°C / min under nitrogen, and kept for 30 hours under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen is 9.6:0.4) to complete the sintering.

[0124] The black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 94% aluminum nitride, 5% sintering aid (including 4% Y2O3 and 1% CaF2) and 1% coloring aid (including 0.3% NbO2 and 0.7% Mo2O3).

[0125] Example 7

[0126] This embodiment provides a method for preparing a black high thermal conductivity aluminum nitride ceramic, which comprises the following steps:

[0127] First, 1 g of Y2O3 powder and 0.5 g of CaF2 powder were weighed and mixed as a sintering aid, and 0.5 g of NbO2 powder, 2 g of Mo2O3 powder and 2.5 g of Cr2O3 powder were weighed and mixed as a coloring aid.

[0128] Then, the sintering aid, coloring aid and 1.5 g oleic acid were mixed with 45 g toluene-isopropanol mixed solvent and wet pre-ball-milled for 2 h, and then 93.5 g aluminum nitride powder (oxygen content 0.65%) was added and ball-milled to obtain sintered powder.

[0129] That is, the mass ratio of the total amount of the ceramic powder consisting of the sintering aid, the coloring aid and the aluminum nitride powder to the toluene-isopropanol mixed solvent used to disperse the ceramic powder is 1:0.45.

[0130] Next, 8 g of polyacrylic acid resin and 4 g of DBP were dissolved in 28 g of a toluene-isopropanol mixed solvent to prepare a polyacrylic acid solution as a composite colloid.

[0131] The fourth step is to add the composite colloid into the sintered powder and fully disperse it by ball milling to obtain aluminum nitride ceramic slurry.

[0132] That is, the mass ratio of the total amount of ceramic powder consisting of sintering aid, coloring aid and aluminum nitride powder to the mass ratio of the polyacrylic acid resin in the composite colloid is 100:8.

[0133] The fifth step is to vacuum degas the aluminum nitride ceramic slurry to a viscosity of 11000 m·Pa·s, and to obtain a green sheet by tape casting.

[0134] In the sixth step, the green sheet is subjected to a debinding treatment in stages to obtain a debinding sheet with an oxygen content of 1.9%.

[0135] Specifically, the temperature was increased to 300°C at a heating rate of 0.5°C / min at a nitrogen ventilation flow rate of 800L / min and kept warm for 1h, and then the temperature was increased to 350°C at a heating rate of 0.05°C / min at a nitrogen-air mixed gas ventilation flow rate of 800L / min (750L / min nitrogen + 50L / min air) and kept warm for 1h to complete the debinding.

[0136] Finally, the stripping film is sintered in stages to obtain black high thermal conductivity aluminum nitride ceramics.

[0137] Specifically, the temperature was increased to 1000°C at a heating rate of 6°C / min under nitrogen, then increased to 1600°C at a heating rate of 2°C / min under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen is 9:1), and finally increased to 1800°C at a heating rate of 0.3°C / min under nitrogen, and kept for 12 hours under a nitrogen-hydrogen mixture (the volume ratio of nitrogen to hydrogen is 9.6:0.4) to complete the sintering.

[0138] The above-mentioned black high thermal conductivity aluminum nitride ceramic obtained in this embodiment is obtained by uniformly mixing and sintering 93.5% aluminum nitride, 1.5% sintering aid (including 1% Y2O3 and 0.5% CaF2) and 1% coloring aid (including 0.5% NbO2, 2% Mo2O3, 2.5% Cr2O3).

[0139] In order to verify the importance of precise control of multiple stages and different atmospheres during debinding and sintering in the above preparation method and to improve the inhibitory effect of coloring additives on the improvement of thermal conductivity, several comparative experiments were carried out.

[0140] Comparative Example 1

[0141] The similarities between this comparative example and Example 1 are not repeated here, and only the differences from Example 1 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 1 is that in the sixth step of debinding, the debinding process is specifically as follows: heating to 300°C at a heating rate of 1°C / min at a nitrogen ventilation flow rate of 800L / min and keeping warm for 1h, and then heating to 350°C at a heating rate of 0.18°C / min at a nitrogen-air mixture flow rate of 800L / min (600L / min nitrogen + 200L / min air), completing debinding, and obtaining a debinding sheet with an oxygen content of 1.92%. The rest is as described in Example 1 to obtain the first comparative black high thermal conductivity aluminum nitride ceramic.

[0142] Comparative Example 2

[0143] The similarities between this comparative example and Example 1 are not repeated here, and only the differences from Example 1 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 1 is that in the sixth step of debinding, the debinding process is specifically as follows: heating to 300°C at a heating rate of 0.5°C / min at a nitrogen ventilation flow rate of 800L / min and keeping warm for 1h, and then heating to 550°C at a heating rate of 0.05°C / min at a nitrogen-air mixture flow rate of 800L / min (500L / min nitrogen + 300L / min air) and keeping warm for 3h, completing the debinding and obtaining a debinding sheet with an oxygen content of 2.1%. The rest is as described in Example 1 to obtain a second comparative black high thermal conductivity aluminum nitride ceramic.

[0144] Comparative Example 3

[0145] The similarities between this comparative example and Example 4 are not repeated here, and only the differences from Example 4 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 4 is that in the last sintering step, the sintering process is specifically as follows: heating to 1000°C under nitrogen at a heating rate of 10°C / min, and then adjusting the atmosphere to nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen is 9.5:0.5) to continue heating to 1550°C, and then heating to 1850°C under nitrogen at a heating rate of 0.5°C / min, and keeping warm for 20 hours under nitrogen-hydrogen (the volume ratio of nitrogen to hydrogen is 9.5:0.5) to complete sintering. The rest is described in Example 4 to obtain a third comparative black high thermal conductivity aluminum nitride ceramic.

[0146] Comparative Example 4

[0147] The similarities between this comparative example and Example 4 are not repeated here, and only the differences from Example 4 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 4 is that in the last sintering step, the sintering process is specifically as follows: heating to 800°C under nitrogen at a heating rate of 10°C / min, then heating to 1550°C at a heating rate of 1°C / min under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen is 9.5:0.5), and finally heating to 1850°C under nitrogen at a heating rate of 5.5°C / min, and keeping warm for 20 hours under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen is 9.5:0.5) to complete the sintering. The rest is described in Example 4 to obtain the fourth comparative black high thermal conductivity aluminum nitride ceramic.

[0148] Comparative Example 5

[0149] The similarities between this comparative example and Example 5 are not repeated here, and only the differences from Example 5 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 5 is that in the last sintering step, the sintering process is specifically as follows: heating to 800°C under nitrogen at a heating rate of 10°C / min, then heating to 1600°C at a heating rate of 3°C / min under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen is 8.5:1.5), and finally heating to 1800°C under nitrogen at a heating rate of 0.3°C / min, and keeping warm for 2.5h under nitrogen-hydrogen gas (the volume ratio of nitrogen to hydrogen is 9.5:0.5) to complete sintering. The rest is described in Example 5 to obtain the fifth comparative black high thermal conductivity aluminum nitride ceramic.

[0150] Comparative Example 6

[0151] The similarities between this comparative example and Example 2 are not repeated here, and only the differences from Example 2 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 2 is that in the last sintering step, the sintering process is specifically as follows: heating to 1400°C at a heating rate of 10°C / min under nitrogen-hydrogen mixed gas (the volume ratio of nitrogen to hydrogen is 8.5:1.5), then keeping warm at 1400°C for 30min, and finally heating to 1700°C at a heating rate of 0.6°C / min under nitrogen, and keeping warm for 150h under nitrogen-hydrogen gas (the volume ratio of nitrogen to hydrogen is 9.5:0.5) to complete sintering. The rest is described in Example 2 to obtain the sixth comparative black high thermal conductivity aluminum nitride ceramic.

[0152] Comparative Example 7

[0153] The similarities between this comparative example and Example 4 are not repeated here, and only the differences from Example 4 are described. The difference between the preparation method provided in this comparative example and the preparation method in Example 4 is that in the last sintering step, the sintering process is specifically as follows: heating to 800°C under nitrogen at a heating rate of 10°C / min, then heating to 1550°C under nitrogen at a heating rate of 8°C / min, and finally heating to 1850°C under nitrogen at a heating rate of 0.5°C / min, and keeping warm for 20h under nitrogen to complete sintering. The rest is as described in Example 4 to obtain the seventh comparative black high thermal conductivity aluminum nitride ceramic.

[0154] The black high thermal conductivity aluminum nitride ceramics provided in Examples 1 to 7 and the comparative aluminum nitride ceramics provided in Comparative Examples 1 to 7 were ground to a thickness of 0.5 mm, placed in a reflectivity tester to weigh, and their reflectivity was measured; the ceramic density was tested using a water displacement density tester; the three-point bending strength was tested using an electronic universal testing machine; and the ceramic thermal conductivity was tested using an instantaneous plane heat source method; the test results are shown in Table 1 below.

[0155] Table 1 Performance test results of aluminum nitride ceramics provided in various embodiments and comparative examples

[0156]

[0157]

[0158] As can be seen from Table 1 above, the aluminum nitride ceramics provided in Examples 1 to 7 all exhibit extremely low reflectivity, that is, they exhibit a darker black color and have a better visible light absorption effect; their thermal conductivity all reaches above 180 W / m·k, showing high thermal conductivity. At the same time, from the test results of their relative density and flexural strength, it can be seen that the performance of the aluminum nitride ceramics has reached the excellent level of existing similar products.

[0159] It can be seen from Table 1 above that, compared with Example 1, Comparative Example 1 takes less time to debind, and the binder is not completely decomposed and removed during the debinding process. During the sintering process, the residual binder causes more impurities to be added during the sintering process, thereby reducing the sintered thermal conductivity of black aluminum nitride.

[0160] Compared with Example 1, in Comparative Example 2, more air was introduced during the debinding process and the heating time and the insulation time were longer, resulting in an oxygen content of 2.1% in the debinding sheet obtained after debinding. During the sintering process, more oxygen impurities and oxygen defects were present in the aluminum nitride crystals, resulting in increased phonon scattering of aluminum nitride and a much lower thermal conductivity than that in Example 1.

[0161] Compared with Example 4, in Comparative Example 3, the temperature is raised too quickly during the sintering process, especially the time for the color development reaction is insufficient, resulting in the inability to effectively dope the coloring auxiliary into the crystals to form color development crystals. As a result, the product obtained in Comparative Example 3 absorbs insufficient visible light, resulting in increased reflectivity, that is, its blackness is not sufficient for use as a black ceramic.

[0162] Compared with Example 4, Comparative Example 4 has a second temperature increase too fast during the sintering process, abnormal grain growth of aluminum nitride powder, decreased grain uniformity, lower thermal conductivity than Example 4, and reduced uniformity of the coloring additive during the sintering process, which also causes a decrease in light efficiency absorption rate and an increase in reflectivity. That is, the product obtained is neither a black ceramic nor a high thermal conductivity ceramic.

[0163] Compared with Example 5, in Comparative Example 5, the holding time after the second heating is shorter in the sintering process, the crystal growth is insufficient, the uniformity is low, and the phonon transmission loss is increased, resulting in lower thermal conductivity.

[0164] Compared with Example 2, in Comparative Example 6, the high-temperature holding time after the second heating is too long in the sintering process, resulting in larger grain growth and higher thermal conductivity of the ceramic substrate. However, excessively large grains will lead to reduced light absorption, thereby increasing reflectivity.

[0165] Compared with Example 4, Comparative Example 7 is sintered in a nitrogen atmosphere throughout the entire process. Since there are factors in the system that are not conducive to thermal conductivity, such as coloring additives, and there is no reducing atmosphere to further remove oxygen defects from the aluminum nitride crystals during the sintering process, the thermal conductivity of the sintered substrate will not reach a high level.

[0166] It can be seen that in the preparation method of the black high thermal conductivity aluminum nitride ceramic provided by the present invention, the debinding and sintering under specific conditions, especially the control of the oxygen content in the debinding sheet after debinding, and the time and atmosphere control of the color development stage and the crystal growth stage during sintering, have an important influence on the final aluminum nitride ceramic product to overcome the adverse effects of the coloring additive on improving the thermal conductivity and to have both the dual characteristics of black and high thermal conductivity.

[0167] The embodiments used above are only for illustrating and explaining the contents of the present invention, and do not constitute any special limitation to the present invention. Any form of modification made without departing from the basic concept of the present invention, as well as the obvious modifications derived therefrom, shall fall within the protection scope of the present invention.

Claims

1. A black high thermal conductivity aluminum nitride ceramic, characterized in that: It is formed by uniformly mixing and sintering aluminum nitride powder, sintering aid and coloring aid in a mass ratio of 90-98:1-5:1-5, and the oxygen content of the aluminum nitride powder before sintering does not exceed 1.9%; wherein the black high thermal conductivity aluminum nitride ceramic has a reflectivity of no more than 14% and a thermal conductivity of more than 180W / m·k.

2. The black high thermal conductivity aluminum nitride ceramic according to claim 1, characterized in that: The oxygen content of the aluminum nitride powder is not higher than 0.7%; the sintering aid is selected from a mixture of at least two of Y2O3, CaF, CaO, MgO, ZnO, and SiO2; the coloring aid is selected from at least one of CeO2, MnO2, MoO2, MoO3, Fe2O3, Fe3O4, Cr2O3, NbO2, HfO2, DyO2, TiO2, Co3O4, and GaO2.

3. A method for preparing black high thermal conductivity aluminum nitride ceramics, characterized in that: The steps include: S1, mixing a sintering aid, a coloring aid, aluminum nitride powder, a binder and a solvent and ball-milling the mixture to obtain a tape-casting slurry; S2, the casting slurry is degassed to a viscosity of 5000m·Pa·s to 18000m·Pa·s, and then cast to obtain a green sheet; S3, heating the green sheet to 300° C. to 600° C. under an inert gas or an inert-air mixed gas, and controlling the process from the beginning of the heating to perform debinding for at least 10 hours to obtain a debinded sheet with an oxygen content not exceeding 1.9%; S4, heating the debonding sheet to 1400°C-1600°C once, and introducing an inert-reducing mixed gas for at least 60 minutes before reaching this temperature to perform a color development reaction, and then heating it for a second time to 1650°C-1950°C for at least 90 minutes, and finally keeping the temperature for 3h-100h, and controlling the total duration of the second heating and keeping the temperature to be no less than 10h, to complete the sintering and obtain the black high thermal conductivity aluminum nitride ceramic.

4. The preparation method according to claim 3, characterized in that: In the casting slurry, the mass ratio of the aluminum nitride powder, the sintering aid and the coloring aid is 90-98:1-5:1-5; the mass ratio of the binder to the total mass of the aluminum nitride powder, the sintering aid and the coloring aid is 0.05-0.12:

1.

5. The preparation method according to claim 3 or 4, characterized in that: In step S3, the temperature of the green sheet is raised to 300° C. to 600° C. by a one-step method or by a multi-step-insulation platform method.

6. The preparation method according to claim 5, characterized in that: In step S3, the green sheet is heated to 300° C. to 600° C. and then kept warm, and the time from the start of heating to the end of keeping warm is at least 10 hours.

7. The preparation method according to claim 3 or 4, characterized in that: In step S4, in one heating, the debonding sheet is heated to 1400° C. to 1600° C. by a one-step method or a multi-step-heat-insulating platform method; In the secondary heating, the debonding sheet after the primary heating is heated for the secondary heating to 1650°C-1950°C by a one-step method, or the debonding sheet after the primary heating is heated for the secondary heating to 1650°C-1950°C by a multi-step-heat-keeping platform method.

8. The preparation method according to claim 7, characterized in that: In step S4, in one heating process, the debonding sheet is heated to 1400° C. to 1600° C. and then kept warm. Before the end of the heat preservation, an inert-reducing mixed gas is introduced for at least 60 minutes to perform a color development reaction.

9. The preparation method according to claim 3, characterized in that: In step S4, in the inert-reducing mixed gas introduced during the color development reaction, the volume content of the reducing gas introduced accounts for 4% to 15% of the total ventilation volume of the inert-reducing mixed gas.

10. The preparation method according to claim 4, characterized in that: The oxygen content of the aluminum nitride powder is not higher than 0.7%; the sintering aid is selected from a mixture of at least two of Y2O3, CaF, CaO, MgO, ZnO, and SiO2; the coloring aid is selected from at least one of CeO2, MnO2, MoO2, MoO3, Fe2O3, Fe3O4, Cr2O3, NbO2, HfO2, DyO2, TiO2, Co3O4, and GaO2; the binder is selected from polyvinyl butyral and / or polyacrylic resin.

Citation Information

Patent Citations

  • Method for making high-thermal-conductivity aluminium nitride ceramics substrate

    CN101333114A

  • Aluminium nitride ceramic substrate, and preparation method thereof

    CN107188568A

  • High-thermal-conductivity aluminum nitride ceramic and preparation method thereof

    CN112939607A

  • Black aluminum nitride ceramic shell for 3D sensor and preparation method of black aluminum nitride ceramic shell

    CN114195523A

  • Black aluminum nitride sinter and its production

    JP1996333163A

Cited By

  • Aluminum nitride ceramic homogeneous joint combining silk-screen printing and liquid phase sintering and preparation method of aluminum nitride ceramic homogeneous joint

    CN121554303A

  • Aluminum nitride substrate with low edge and corner cracking rate and preparation method thereof

    CN121698659A